Orientation, composition, and entrapment conditions of fluid inclusions in the footwall of the northern Snake Range detachment, Nevada. (December 2015) - Carter, Matthew J.; Siebenaller, Luc; Teyssier, Christian
Abstract: Footwall rocks of the northern Snake Range detachment fault (Hampton and Hendry's Creeks) offer exposures of quartzite mylonites (sub-horizontal foliation) that were permeated by surface fluids. An S–C–C′ mylonitic fabric is defined by dynamically recrystallized quartz and mica. Electron backscatter diffraction analyses indicate a strong preferred orientation of quartz that is overprinted by two sets of sub-vertical, ESE and NNE striking fractures. Analyses of sets of three perpendicular thin sections indicate that fluid inclusions (FIs) are arranged according to macroscopic fracture patterns. FIs associated with NNE and ESE-striking fractures coevally trapped unmixed CO2 and H2 O-rich fluids at conditions near the critical CO2 –H2 O solvus, giving minimum trapping conditions of T = 175–200 °C and ∼100 MPa H2 O-rich FIs trapped along ESE-trending microcracks in single crystals of quartz may have been trapped at conditions as low as 150 °C and 50 MPa indicating the latest microfracturing and annealing of quartz in an overall extensional system. Results suggest that the upper crust was thin (4–8 km) during FI trapping and had an elevated geotherm (>50 °C/km). Footwall rocks that have been exhumed through the brittle-ductile transition in such extensional systems experience both brittle and crystal-plastic deformation that may allow for circulation of meteoric fluids and grain-scale fluid–rock interactions. Highlights: The footwall of the northern Snake Range detachment was permeated by surface fluids. Crystal plastic microstructures, brittle fractures, and fluid inclusions were studied. Fluid circulation and grain-scale interactions may be related to deformation cycles.